Pengaruh Overconfidence, Herding, Availability Bias, Risk Aversion dan Personal Information Terhadap Keputusan Investasi - Wisnu Yuwono; Nadya Altiyane (Program Studi Manajemen Universitas Fajar, 2023)
This study aims to analyze the effect of overconfidence, herding, availability bias, risk aversion, and personal information on stock investment decisions among students in the city of Batam. The objects in this study are students in the city of Batam who invest in stocks. The variables used in this study consisted of independent variables, namely overconfidence, herding, availability bias, risk aversion, and personal information. While the dependent variable is the investment decision. In this study, the authors took 198 respondents' data using a questionnaire to be analyzed using the SPSS version of 24.0 software application. The results of the data in this study indicate overconfidence, risk aversion and personal ?nformation have a significant positive effect on investment decisions, while herding and availability bias do not significantly affect investment decisions. This shows that students as investors already have sufficient knowledge when investing, they are very confident in investing, and are more careful in managing the risks that arise, and more careful in finding relevant information. Keywords : Investment Decision, Overconfidence, Herding, Availability bias, Risk aversion, and Personal Information